Clinical and electroencephalographic characteristics of neurodegeneration with brain iron accumulation type 5 in children on the example of 5 cases - N. Yu. Perunova; M. Yu. Bobylova; T. M. Prygunova (Русский журнал детской неврологии, 2020)
Neurodegenerative disease with brain iron accumulation type 5 (OMIM: 300894) manifests itself with early-onset epilepsy, mental retardation with stereotypies that resemble Rett syndrome, and motor disorders under the mask of cerebral palsy in childhood; since adolescence, patients usually have aggravation of parkinsonism and develop complications, such as torsion dystonia. We analyzed medical records of 5 female patients aged between 2.5 and 6 years. There were no family relationships between patients’ families. All children had problems with their motor skills: 4 out of 5 patients could only crawl; none of them could walk independently. We also observed severe speech disorders in these patients: they had no expressive speech along with reduced understanding of speech. Their behavior was characterized by contact disorders and multiple stereotypies. All children had no self-service skills. The assessment of neurological status demonstrated uniform symmetrical paresis (score 3–4; 100 % of cases), increased muscle tone of the extrapyramidal type (40 % of cases), and diffuse muscle hypotension with ataxia (40 % of cases). One patient (with autistic-like behavior) had no motor disorders. Magnetic resonance imaging showed non-specific changes in 100 % of cases (diffuse cortical / subcortical atrophy, secondary hydrocephalus ex vacuo). One patient was found to have hypointense signal in the substantia nigra and globus pallidus on follow-up T2‑weighted magnetic resonance images obtained at the age of 6 years. All patients presented with epilepsy: West syndrome (n = 1), Lennox–Gastaut syndrome (n = 1), focal epilepsy with asymmetric tonic seizures (n = 1), and focal epilepsy with febrile generalized tonic-clonic seizures (n = 2). Remission for more than 1 year was achieved in 4 out of 5 patients. The following electroencephalographic patterns were identified before treatment initiation: hypsarrhythmia with transformation into epilepsy with a pattern of continued spike-and-wave activity during sleep (n = 1), multi-regional epileptiform activity with a tendency to diffuse spread and predominance in the frontal region (n = 3), and regional epileptiform activity in the frontocentral area (n = 1). The initial therapy with first-line drugs was highly effective and ensured remission in 3 patients; one patient had remission in response to hormone therapy; one patient continued to have seizures despite polytherapy with antiepileptic drugs. Interictal epileptiform activity was completely blocked by treatment in 2 cases; the rest of the patients had transformation of epilepsy into benign epileptiform discharges of childhood (n = 3).